PEMANFAATAN MEDIA INFOGRAFIS SEBAGAI UPAYA MENUMBUHKAN KARAKTER PEDULI LINGKUNGAN PADA PESERTA DIDIK SD - Ardalia Putri Fauziah,; Ghina Rifqatul Alawiya,; Sephia Nisa Syaharani,; Martini, Martini (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to determine the use of infographic media as an effort to foster a caring character for the environment in elementary school students. The method used in this study is the method of literature review or literature review with secondary data collection techniques. Secondary data in this study are in the form of several national and international journals related to the Utilization of Infographic Media as an Effort to Grow Environmental Care Character in Elementary School Students and using sources found on web pages. In analyzing the validity of the data, a gradual analysis was carried out, namely data collected from the results of research articles then data reduction, data display, and finally data conclusions. The data presented include: a) Forms of implementing environmental care in elementary schools, (b) Factors for selecting infographics as a medium for cultivating environmental care characters in elementary school students, (c) Supporting and inhibiting factors for the implementation of environmental care characters in elementary school students. There are various forms of implementing environmental care in elementary schools which include the 3R program (Reduce, Reuse, and Recycle), Go Green, LISA (See Take Garbage), and Healthy Canteens, Talambotik (Plants in plastic bottles). The conclusion is that one of the efforts to cultivate a caring character for the environment is to socialize elementary students through infographic media. This infographic media is more effective and efficient because infographic media can be presented in a visual form, packaged in clear and accessible language for readers to understand as well as a display that attracts the interest of elementary school students.